Hybrid AC/DC microgrid GUI development and database design - Wang, Xiaochen. (2013)
Although the pollution from the conventional combustion driven generators have been significantly reduced through several modified post-process on the pollutant, the Green House Effect and high Particle Matter index are still severe in recent years. Solar, Wind and Fuel Cell Energy Resources have been investigated for decades and the related technologies have been developed to integrate them to AC power grids. The concept of Hybrid Micro Grid has been come up with to combine both AC and DC Networks with according sources and loads connected and to facilitate the integration AC and DC generation and loads with optimal operation efficiency.